First in human neochordae retensioning for recurrence of mitral regurgitation after neochord procedure - Fiocco, Alessandro; Pittarello, Demetrio; D’Onofrio, Augusto; Mastro, Florinda; Gerosa, Gino; Colli, Andrea (Frontiers in Cardiovascular Medicine, 2023)
Neochord Procedure is a viable option to treat degenerative mitral valve regurgitation, in selected patients. Left-ventricle-reverse-remodeling can cause neochord-relative-elongation and reprolapse of the treated leaflet, leading to failure. We present a clinical case of abnormal extensive ventricle-reverse-remodeling after neochord implantation and the first-in-man off-pump surgical retensioning of the previously implanted artificial chords.